Recurrent Gallbladder Carcinoma With pMMR/MSS Achieved a Complete Response Following Camrelizumab Combined With Apatinib: A Case Report - Zhong, Liting; Liu, Xiaoyu; Li, Zelei; Zhang, Xuebing; Wang, Yuli; Peng, Weiwei (Frontiers in Oncology, 2022)
Gallbladder carcinoma (GBC) with proficient mismatch repair (pMMR)/microsatellite stable (MSS) is associated with limited response to programmed death -1 (PD-1) inhibitor monotherapy. Limited data of PD-1 blockade combined with anti-angiogenic therapy in GBC is reported. One recurrent GBC patient with pMMR/MSS was treated with camrelizumab plus apatinib. After 4 cycles of combination therapy, the patient achieved a durable complete response with manageable toxicity. The next generation sequencing and immunohistochemistry analysis showed that tumor mutation burden (TMB) was 7.26 Mutants/Mb and PD-L1 expression was 10% (tumor proportion score) and 20% (immune proportion score). This case suggests that camrelizumab in combination with apatinib may be an effective treatment option for GBC patients with pMMR/MSS status, who have moderate expression of TMB and PD-L1. Additionally, TMB and PD-L1 expression may serve as potential biomarkers for predicting PD-1 inhibitor response of GBC. Furthermore, this needs to be verified in future studies.